South African marine citizen science – benefits, challenges and future directions. Issue 3 (3rd July 2021) - Potts, WM; Mann-Lang, JB; Mann, BQ; Griffiths, CL; Attwood, CG; de Blocq, AD; Elwen, SH; Nel, R; Sink, KJ; Thornycroft, R
Abstract : South Africa has a long history of engagement in citizen science (CS), particularly marine CS. This review examines the contributions made by marine CS, from the 1930s through to the current era, where websites, social media and mobile apps provide a wide range of opportunities. Largescale marine CS projects, such as the Oceanographic Research Institute's Cooperative Fish Tagging Project, have made enormous contributions to marine scientific research. Individual citizen scientists have also made considerable contributions, particularly in taxonomy and the publication of field guides. Marine CS has also contributed towards the popularisation of science and improved scientific literacy through the active engagement of many citizens. These benefits align well with the visions of policies that currently guide the South African marine research agenda. However, marine CS in the developing world is not without challenges, and practitioners should be cognisant of the time and effort required to initiate and maintain viable CS initiatives. Especially, long-term successful CS projects depend on secure, ongoing funding, institutional support and enthusiastic champions. Participation by almost exclusively the urban and middle-class sectors of society is also of concern. These challenges can be addressed through stakeholder-inclusive planning, development of novel methods that engage with broader sectors of society, and regular critical evaluations of CS projects. Where global projects on the intended taxa/subject of study already exist, it may also be preferable to enter into collaborative data-sharing agreements with these to reduce operational costs and avoid duplication.